RESEARCH OF GOLD EXTRACTION TECHNOLOGY FROM TECHNOGENIC RAW MATERIAL - A.K. Koizhanova; B.K. Kenzhaliyev; E.M. Kamalov; M.B. Erdenova; D.R. Magomedov; N.N. Abdyldaev (Academic Scientific Journal of Chemistry, 2020)
The results of the leaching of the tailings from the heap leaching section with the aim of extracting gold associated with sulfides are presented. A representative sample of the tailings of the heap leaching section was selected and its chemical, phase, and mineralogical composition were studied. It was established that the test sample contains 1.2 g / t Au. According to a rational analysis, by sorption cyanidation at a fineness of 95% class minus 0.071 mm, 76.09% of gold is extracted from a sample of heap leaching tailings, which is mainly (71.74%) represented by intergrowths with ore and rock-forming components. The mass fraction of free (amalgamable noble metal is insignificant (4.35%). The main reason for the persistence to sorption cyanidation is the close association of gold with sulfide minerals. In the optimal mode of cyanidation of oxidation residues, 71.7 % of gold is recovered in 24 hours